Nonswelling Lubricative Nanocolloidal Hydrogel Resistant to Biodegradation - Ding, Tiantian; Ren, Chunxia; Meng, Liyuan; Han, Guoyong; Xue, Yao; Song, Wenlong; Li, Daowei; Sun, Hongchen; Yang, Bai; Li, Yunfeng (Nano-Micro Letters, 2025)
Hydrogels derived from biopolymers have numerous applications in bioengineering, drug delivery, wound healing, and wearable devices. Yet, their strong swelling and uncontrollable degradation stimulate the development of hydrogels that overcome these limitations. Here, we report nanocolloidal hydrogels formed from nanoparticles of methacryloyl-modified biopolymers that exhibit resistance to swelling and enzymatic degradation both in vitro and in vivo, along with exhibiting a broad-range of mechanical and lubrication properties, wear resistance and biocompatibility. The nonswelling behavior of nanocolloidal hydrogels takes origin in the resistance to swelling of their hydrophobic regions which are resulted from the nanophase of hydrophobic methacryloyl groups in the interior of the constituent nanoparticles. The developed approach to the preparation of nanocolloidal hydrogel with greatly enhanced properties will have applications in long-term drug delivery and cell culture, soft tissue augmentation, and implantable bioelectronics. Highlights: 1 Novel nanocolloidal hydrogels form nanoparticles of methacryloyl-modified biopolymers. 2 The nanocolloidal hydrogels exhibit tunable mechanical properties, nonswelling behavior, excellent biodegradation resistance, and good biocompatibility. 3 The nanocolloidal hydrogels show outstanding lubrication with a friction coefficient as low as ~ 0.0018.